Words on fire - Nielsen, Jennifer A. (New York: Scholastic Press, 2019)
In 1893 twelve-year-old Audra lives on a farm in Lithuania, and tries to avoid the Cossack soldiers who enforce the Russian decrees that ban Lithuanian books, religion, culture, and even the language; but when the soldiers invade the farm Audra is the only one who escapes and, unsure of what has happened to her parents, she embarks on a dangerous journey, carrying the smuggled Lithuanian books that fuel the growing resistance movement, unsure of who to trust, but risking her life and freedom for her country.
820L
3-6
5.8
V
Keywords: Smuggling -- Lithuania -- Juvenile fiction; Books and reading -- Juvenile fiction; Government, Resistance to -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Lithuania -- History -- 19th century -- Juvenile fiction; Lithuania -- History -- Underground movements -- Juvenile fiction; Action and adventure fiction; Action and adventure fiction; Historical fiction